An Efficient One-Pot Synthesis of Spiro [indole-pyrazolobenzothiazepine] Derivatives in Ionic Liquid Using Amberlyst-15 As a Reusable Catalyst - Dandia, Anshu; L. Gupta, Shyam; K. Jain, Anuj (Current Green Chemistry, 2014)
A novel methodology for the synthesis of privileged medicinal scaffolds 1,5-benzothiazepine derivatives using amberlyst-15 as a heterogeneous catalyst in ionic liquid as solvent is reported. In this report, substituted 2- aminothiophenols react with 3-pyrazolidinyl-2H-indol-2-one generated in situ from indole-2,3-dione and 3-methyl-1- phenylpyrazoline-5-one to furnish spiro azathiaheterocycles. The catalytic system can be easily recycled and reused for at least four times without significant loss of yields and reactivity. Interestingly, title compounds were not achieved, when the reactions were carried out conventionally using volatile organic solvents.
Keywords: Amberlyst-15